A bibliometric analysis of house price research - Tachaini, Subramaniam (2021)
House Price studies have gained popularity among researchers throughout the world. However, there is limited number of comprehensive bibliometric analysis conducted in this area. The main objective of this study is to provide a comprehensive analysis on visualized bibliometric and Scientometric view of house price research. Scopus database was used to extract the data of 4284 publications from 1954 till 13th February 2021. VOSviewer software was then used to analyze and visualize the data. The result revealed a significant increase in the annual number of house price studies with, Gupta.R has been identified as the top author involving in the publication on house price and also collaborate with other authors such as Miller S.M, Apegis.N and Chang.T to conduct the research. The United States were identified as the most active country in publication on house price and it can be visualized clearly that United States is working closely with the other countries as well such as United Kingdom and Australia to published more research on house price. The results of this study also reveal the top keywords that are used by the authors are “house prices”, “housing market” and “housing”. Journal of Real Estate Finance and Economics is identified as the most active journals in publishing on house price and Journal of Urban Economics were identified as journal that are highly co cited according to the related sources. By comparing the publication scales and co networks, this study provides an overview on house price in term of bibliometric analysis and future research directions.